Hiking Trails Facilitate the Spread of a Native High‐Arctic Species - Deborah Zani; Heike Lischke; Jonas Åkerman; Veiko Lehsten (Ecology and Evolution)
ABSTRACT High‐Arctic environments are facing an elevated pace of warming and increasing human activities, making them more susceptible to the introduction and spread of alien species. We investigated the role of human disturbance in facilitating the spread of a native plant (Papaver dahlianum) in a high‐Arctic natural environment close to Isfjord Radio station and along adjacent hiking trails at Kapp Linné, Svalbard. We reconstructed the spatial pattern of the arrival and spread of P. dahlianum at Kapp Linné by combining historical records of the species occurrence (1928–2018) with a contemporary survey of the plant abundance along the main hiking trail (2023 survey) and tested the relative effects of altitude and proximity to hiking trails on the species density via a generalised linear model (GLM). We then compared historical records with the simulated annual spread of the species by assuming either only local spread or local spread plus spread from hiking trails. Finally, we used a fine‐scale UAV‐derived brightness index to test for terrain preference by applying a randomisation test. Distance from the station (56% explained variation) and minimum distance from the trail (28%) significantly explained the species density across the research area (best GLM R2 = 0.755). The modelled species spread including the trail effect (fitted spread ~30 m yr.−1) managed to capture the maximum extent of the occupied area, whereas simulations assuming only local spread (~2 m yr.−1) underestimated the historical extent. A randomisation test showed that P. dahlianum has a significant preference for gravel soils with low vegetation cover due to either trail trampling and/or natural processes. Along with climate warming, human activities can increase the rate of species range shift by providing hot spots of introduction (human settlements) and spreading corridors (hiking trails). Our results show that spatially explicit models can be applied to accurately predict the potential spread of species, leading to a more efficient monitoring plan. Systematic monitoring of alien species and sanitisation measures should be prioritised in polar habitats with a high incidence of human disturbances.